Determinants of Capital Structure and their Effect on Firm Value: Evidence on Food and Beverage Companies in Indonesia - Zahri, Cut; Sopang, Fandi Iskandar; Irwandi, Bambang (Universitas Mercu Buana, 2024)
Objectives: In this study, capital structure is used as an intermediary variable to examine how liquidity, profitability, and company size affect firm value. This study is anticipated to serve as a resource for future research as well as help businesses and investors make a variety of decisions.Methodology: This study uses secondary data and is quantitative. These facts were gathered via documentation methods. All of the firms in the food and beverage sectors that are listed on the IDX 2020–2021 make up the study's population. Purposive sampling was used to collect samples from 158 observations.Finding: According to the study's findings, liquidity, profitability, firm size, and capital structure had an impact on share value while only partially having an impact on capital structure. The outcomes of the path analysis demonstrate that while profitability has an impact on share value mediated by capital structure, liquidity, and company size do not have an impact on share value.Conclusion: Future researchers are urged by the findings of this study to include other variables, including external variables like inflation, interest rates, and taxes which may have an impact on business value